2008
DOI: 10.1097/nmd.0b013e31816a4952
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Cultural Study of Conviction Subtype Taijin Kyofu

Abstract: Conviction subtype Taijin-Kyofu (c-TK) is a subgroup of mental disorder characterized by conviction and strong fear of offending others in social situations. Although the concept of c-TK overlaps with that of social anxiety disorder (SAD), patients with c-TK often may not be diagnosed as such within the current DSM-IV criteria. We propose the Nagoya-Osaka Criteria to amend this situation. This study examined the cross-cultural inter-rater reliability of the proposed criteria. 18 case vignettes of patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The current WHO-CIDI 3.0 does not specifically assess the TSK, but diagnoses and symptoms of TKS and social anxiety disorder often overlaps [Kinoshita et al, 2008; Kleinknecht et al, 1997]. This possibility should also be addressed in future research.…”
Section: Discussionmentioning
confidence: 99%
“…The current WHO-CIDI 3.0 does not specifically assess the TSK, but diagnoses and symptoms of TKS and social anxiety disorder often overlaps [Kinoshita et al, 2008; Kleinknecht et al, 1997]. This possibility should also be addressed in future research.…”
Section: Discussionmentioning
confidence: 99%
“…The difficulty in distinguishing SA from psychosis in some cases reveals the fragility of diagnostic constructs and the current psychopathological models. Of the third case's particular situation, some authors [ 9 ] have observed this presentation as an "offensive SAD subtype", which also includes patients with (delusional) conviction of offensiveness. Such concepts are the product of a syndrome recognized in Japan since 1930 as "Taijin-Kyofu" (TK) [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Its "conviction subtype" is characterized by a strong belief and fear that others are disturbed by the individual's inadequacy. This inadequacy could occur in several ways due to the emission of body odors, facial expressions, intestinal noises, and so forth [ 9 ]. Among Western psychiatrists guided by the DSM-IV, such a condition can only be diagnosed as a DD.…”
Section: Discussionmentioning
confidence: 99%
“…In their efforts to clarify the difference between SAD and TKS, Kinoshita et al ( 2008 ) proposed a conceptual model that divides SAD into subtypes. According this model, SAD is first divided based on whether or not offensive symptoms are present.…”
Section: Nature Of Egorrheamentioning
confidence: 99%